Object-Oriented Programming with Java - Curry, Caleb (Addison-Wesley Professional, 2020)
5+ Hours of Video Instruction Java was introduced to the open-source community more than 20 years ago, and it remains popular among developers. However, we now live in a world dominated by the cloud, mobile, IoT, and open source, where containers, Kubernetes, microservices, reactive, and cloud-native application development can deliver higher levels of productivity and efficiency. That's where OOP concepts take center stage, and what Caleb concentrates on in this LiveLessons. Description In Object-Oriented Programming with Java LiveLessons, Caleb Curry provides the foundational instruction on OOP design principles and concepts, applying them in Java, so that programmers can overcome the challenges of starting or moving to OOP. Because modern languages are designed for scalability, Caleb describes how to think about coding with scalability in mind. He introduces classes, objects, methods, fields, access modifiers, encapsulation, polymorphism, and inheritance. He also covers some of the best practices around exception handling in the context of object-oriented programming for Java up through Java SE 14. About the Instructor Caleb Curry has taught thousands of people programming principles through his YouTube channel and social channels. He works with numerous programming languages and has developed a following and reputation as a guru in coding and technology. His simple approach to teaching delights audiences of 190,000 subscribers on YouTube. He also produces courses with Pearson (Getting Started with MongoDB and NoSQL LiveLessons) and has been featured in Forbes . Website: http://calebcurry.com YouTube: https://youtube.com/calebthevideomaker2 LinkedIn: https://www.linkedin.com/in/calebcurry Skill Level Beginning to Intermediate What You Will Learn Learn the common terminology of object-oriented programming Develop example code for the main keywords Learn how the Java language is structured to build code to your full potential Build Java applications that use object-oriented principles Learn to encapsulate data using various Java keywords Design an inheritance hierarchy and implement it in code Understand polymorphism and how to get the most from your inheritance hierarchy Conquer the vast number of access modifiers to ensure the integrity of your code Who Should Take This Course Programmers Developers (getting started with OOP concepts, but aware of programming in general) Course Requirements Prerequisites: Familiarity with t ...